The city as a common good: Ideas e ideals - Cunha, Camila Marques Paes da; Gonçalves, Luciana Márcia (Revista Nacional de Gerenciamento de Cidades, 2021)
The contemporary urbanization process in Brazil is directly related to the dynamics of the capitalist production mode. In this production mode the urban land, as well as habitation, become commodities – individual or collective consumer goods. With the increase in municipal autonomy back in the 1990s, along with the approval of the Statue of Cities in 2001, new tools for organization of urban territory and production of habitations were created. This work makes a brief analysis of the right to city’s trajectory, since the creation of such concept by Henri Lefebvre in the 1960s, until the concept’s appropriation by Brazilian legislation. Through bibliographical review, it relates the social role of property as means to grant the right to the city.